The Effect of Inflation on the Rate of Economic Growth - Enzelina Sitanggang; Janisa Aulia; Khairani Alawiyah Matondang; Riza Indriani (PT FORMOSA CENDEKIA GLOBAL, 2022)
The relationship between inflation and economic growth is interrelated. If high inflation can cause economic growth to slow down, on the other hand relatively low and stable inflation can encourage economic growth. The results of the analysis show that economic growth is influenced by population growth and inflation. Population growth has a significant negative impact on economic growth. Inflation in Indonesia fluctuates from year to year due to high inflation so that people who are initially able to meet their daily needs with exorbitant prices for goods and services cannot fulfill their needs, which leads to poverty.